2008
DOI: 10.2119/2007-00093.owuor
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Immune Complex Binding Capacity and Increased Complement Susceptibility of Red Cells from Children with Severe Malaria-Associated Anemia

Abstract: Plasmodium falciparum malaria causes 1-2 million deaths per year. Most deaths occur as a result of complications such as severe anemia and cerebral malaria (CM) (coma). Red cells of children with severe malaria-associated anemia (SMA) have acquired deficiencies in the complement regulatory proteins complement receptor 1 (CR1, CD35) and decay accelerating factor (DAF, CD55). We investigated whether these deficiencies affect the ability of erythrocytes to bind immune complexes (ICs) and regulate complement activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 26 publications
(43 reference statements)
0
36
0
Order By: Relevance
“…4). Indeed, higher C3b deposition on cells with low CR1 and subsequently enhanced complement-mediated damage and phagocytosis in spleen has recently been demonstrated for RBCs from children with severe malarial anemia [40]. On the other hand, high RBC CR1 levels could cause greater risk of cerebral malaria as a result of increased CR1-mediated rosetting causing obstruction of blood flow in brain capillaries (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…4). Indeed, higher C3b deposition on cells with low CR1 and subsequently enhanced complement-mediated damage and phagocytosis in spleen has recently been demonstrated for RBCs from children with severe malarial anemia [40]. On the other hand, high RBC CR1 levels could cause greater risk of cerebral malaria as a result of increased CR1-mediated rosetting causing obstruction of blood flow in brain capillaries (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In malaria, decreased levels of CR1 expression on erythrocytes are considered an important factor in the accumulation of IC during disease (39, 40), because of the contribution of erythrocyte CR1 in IC clearance. Erythrocytes transfer IC to macrophages for degradation, probably by transferring the IC from erythrocyte CR1 to macrophage CR1 (41).…”
Section: Discussionmentioning
confidence: 99%
“…Seventy‐five SMA and 32 CM cases were enrolled and matched to 74 and 52 symptomatic uncomplicated malaria controls, respectively. The demographics and clinical characteristics of the study participants were recently reported (10). The mean age (SD) for SMA cases was 16·9 (13·7) months and that of their controls was 16·8 (13·3) months.…”
Section: Resultsmentioning
confidence: 99%
“…The study had a matched case‐control design. In comparison to our previous studies, we modified the case definition for SMA cases from Hb ≤ 5 g/dL to Hb ≤ 6 g/dL to increase the probability of finding red cells with complement (C3) deposition in support of other studies (10). Thus, SMA cases, defined as children with asexual P. falciparum parasitemia by Giemsa‐stained thick and thin blood smear and Hb ≤ 6 g/dL, were recruited from the paediatric ward of the Nyanza Provincial General Hospital (NPGH), Kisumu, Kenya, where malaria is holoendemic.…”
Section: Methodsmentioning
confidence: 96%